Proceso de diagnóstico para la implementación de estrategias de continuidad de negocio en la dirección de operaciones de UNE EPM Telecomunicaciones (2011)
The proposal developed in this monograph rises to meet the current demands of TIC’s market to ensure excellent standards in services delivery. The great services offer makes the market becomes increasingly competitive and it is at this point that companies preparation to face events that compromise the quality levels becomes essential and a great differentiator. It happens in some cases that, only until they face a crisis, they realize that a process of business continuity could have been the key factor that might have prevented the situation and keep them on stage. It is because of this reason that through all three chapters we present a methodology to evaluate current diagnosis of the processes of the company's operations and propose corrective strategies, all based entirely on the concepts of Business Continuity Management Firstly, we establish a general background on the whole concept of business continuity followed by a diagnosis based on the methodology process. Finally, we present the results and suggest strategies always looking to minimize risk and create a culture of business continuity through the critical processes of the operation.